Make/shift Pedagogies: Suggestions, Provocations, and Challenges for Teaching Introductory Gender and Women’s Studies Courses - Olwan, Dana M.; Keating, AnaLouise; Orr, Catherine M.; Guy Sheftall, Beverly (Atlantis, 2016)
Drawing on over four decades of diverse teaching experiences as well as our recent work facilitating the NWSA Curriculum Institute, this article discusses some of the politics and praxis of teaching the introductory Gender and Women’s Studies course in the U.S. academic classroom. While mapping different pedagogical strategies, it offers some suggestions, recommendations, and provocations that inform our commitment to design syllabi, plan courses, and teach materials that introduce students to formative works and concepts in Gender and Women’s Studies, chart current trends, and signal new developments in the field.